Dynamic Mechanism of Proton Transfer in Mannitol 2-Dehydrogenase from Pseudomonas fluorescens: MOBILE GLU(292) CONTROLS PROTON RELAY THROUGH A WATER CHANNEL THAT CONNECTS THE ACTIVE SITE WITH BULK SOLVENT - Klimacek, Mario (American Society for Biochemistry and Molecular Biology, 2012)
The active site of mannitol 2-dehydrogenase from Pseudomonas fluorescens (PfM2DH) is connected with bulk solvent through a narrow protein channel that shows structural resemblance to proton channels utilized by redox-driven proton pumps. A key element of the PfM2DH channel is the “mobile” Glu(292), which was seen crystallographically to adopt distinct positions up and down the channel. It was suggested that the “down → up” conformational change of Glu(292) could play a proton relay function in enzymatic catalysis, through direct proton shuttling by the Glu or because the channel is opened for water molecules forming a chain along which the protons flow. We report evidence from site-directed mutagenesis (Glu(292) → Ala) substantiated by data from molecular dynamics simulations that support a role for Glu(292) as a gate in a water chain (von Grotthuss-type) mechanism of proton translocation. Occupancy of the up and down position of Glu(292) is influenced by the bonding and charge state of the catalytic acid base Lys(295), suggesting that channel opening/closing motions of the Glu are synchronized to the reaction progress. Removal of gatekeeper control in the E292A mutant resulted in a selective, up to 120-fold slowing down of microscopic steps immediately preceding catalytic oxidation of mannitol, consistent with the notion that formation of the productive enzyme-NAD(+)-mannitol complex is promoted by a corresponding position change of Glu(292), which at physiological pH is associated with obligatory deprotonation of Lys(295) to solvent. These results underscore the important role of conformational dynamics in the proton transfer steps of alcohol dehydrogenase catalysis.